Adaptive algorithm based on antenna arrays for radio communication systems - Fedosov, Valentin; Legin, Andrey; Lomakina, Anna (Serbian journal of electrical engineering, 2017)
Trends in the modern world increasingly lead to the growing popularity of wireless technologies. This is possible due to the rapid development of mobile communications, the Internet gaining high popularity, using wireless networks at enterprises, offices, buildings, etc. It requires advanced network technologies with high throughput capacity to meet the needs of users. To date, a popular destination is the development of spatial signal processing techniques allowing to increase spatial bandwidth of communication channels. The most popular method is spatial coding MIMO to increase data transmission speed which is carried out due to several spatial streams emitted by several antennas. Another advantage of this technology is the bandwidth increase to be achieved without expanding the specified frequency range. Spatial coding methods are even more attractive due to a limited frequency resource. Currently, there is an increasing use of wireless communications (for example, WiFi and WiMAX) in information transmission networks. One of the main problems of evolving wireless systems is the need to increase bandwidth and improve the quality of service (reducing the error probability). Bandwidth can be increased by expanding the bandwidth or increasing the radiated power. Nevertheless, the application of these methods has some drawbacks, due to the requirements of biological protection and electromagnetic compatibility, the increase of power and the expansion of the frequency band is limited. This problem is especially relevant in mobile (cellular) communication systems and wireless networks operating in difficult signal propagation conditions. One of the most effective ways to solve this problem is to use adaptive antenna arrays with weakly correlated antenna elements. Communication systems using such antennas are called MIMO systems (Multiple Input Multiple Output multiple input - multiple outputs). At the moment, existing MIMO-idea implementations do not always noticeably accelerate traffic at short distances from the access point, but, they are very effective at long distances. The MIMO principle allows reducing the number of errors in radio data interchange (BER) without reducing the transmission rate under conditions of multiple signal re-reflections. The work aims at developing an adaptive space-time signal algorithm for a wireless data transmission system designed to improve the efficiency of this system, as well as to study the efficiency of the algorithm to minimizing the error bit probability and maximizing the channel capacity. nema